Microwave characterization of pandanus atrocarpus as potential organic-based dielectric substrate - Mohd Aziz Aris; Nurfarahin Miswadi; Suhaila Subahir; Hajar Jaafar; Fatimah Nur Mohd Redzwan (International Journal of Electrical and Computer Engineering (IJECE), 2022)
This study investigated the microwave characterization of a potential organic-based substrate pandanus atrocarpus. Pandanus atrocarpus, also known as "pandan mengkuang", is easily found at riverside and beach areas in Penisular Malaysia. The experiment's objective was to measure dielectric constant and tangent loss using the dielectric coaxial probe method by employing vector network analyzer (VNA) and dielectric probe. Dielectric constant and tangent loss are the crucial parameter in the microwave design. Three different samples of pandanus atrocarpus were measured and analyzed. The result showed that the dielectric constant of the pandanus substrate material depended on the leaves' water content. All experimental results obtained were analyzed, presented, and discussed in this paper.